Efektivitas Media Bungker Terhadap Pemahaman Konsep Tabung-Kerucut Pada Siswa Kelas VI - Dicky Amirul Hasan; Lovika Ardana Riswari; Eka Zuliana (Pendidikan Matematika Universitas PGRI Yogyakarta, 2025)
Geometry learning, especially on the volume of cylinders and cones in elementary schools is often faced with obstacles in students' conceptual understanding, mainly due to ineffective learning methods, such as lectures and the use of limited two-dimensional media. The purpose of this study was to improve students' conceptual understanding of grade VI on the material of cylinders and cones using the